Application of anti-fungal vaccines as a tool against emerging anti-fungal resistance - Kumar, Ravinder; Srivastava, Vartika (Frontiers in Fungal Biology, 2023)
After viruses and bacteria, fungal infections remain a serious threat to the survival and well-being of society. The continuous emergence of resistance against commonly used anti-fungal drugs is a serious concern. The eukaryotic nature of fungal cells makes the identification of novel anti-fungal agents slow and difficult. Increasing global temperature and a humid environment conducive to fungal growth may lead to a fungal endemic or a pandemic. The continuous increase in the population of immunocompromised individuals and falling immunity forced pharmaceutical companies to look for alternative strategies for better managing the global fungal burden. Prevention of infectious diseases by vaccines can be the right choice. Recent success and safe application of mRNA-based vaccines can play a crucial role in our quest to overcome anti-fungal resistance. Expressing fungal cell surface proteins in human subjects using mRNA technology may be sufficient to raise immune response to protect against future fungal infection. The success of mRNA-based anti-fungal vaccines will heavily depend on the identification of fungal surface proteins which are highly immunogenic and have no or least side effects in human subjects. The present review discusses why it is essential to look for anti-fungal vaccines and how vaccines, in general, and mRNA-based vaccines, in particular, can be the right choice in tackling the problem of rising anti-fungal resistance.